Structural, morphological, and optical properties of TiO2 thin films grown by atomic layer deposition on fluorine doped tin oxide conductive glass - Chiappim W. (2016)
© 2015 Elsevier Ltd. All rights reserved.TiO2 thin films were deposited on FTO glass by ALD technique using titanium tetrachloride and water as precursors. A thorough investigation of the TiO2/FTO film properties was carried on, varying the process temperature in the range (150-400)°C and keeping fixed at 2000 the number of reaction cycles. TiO2 films were also grown on Si(100) and glass substrates for some comparisons. RBS, GIXRD, Raman spectroscopy, SEM, AFM and spectrophotometry analyses were performed to investigate the growth per cycle (GPC), composition, structure, morphology and optical properties of the as-deposited films. Through elemental composition analysis was possible to observe that amorphous and rutile films have a deficiency of oxygen. Pure-anatase TiO2 films can be obtained at process temperatures in the range 250-300°C, while for temperatures higher than 300°C rutile phase starts to appear which turns to unique crystalline phase at temperature higher than 350°C. AFM results shows that FTO substrate tends to restrict the size of crystallite growth, and therefore, the grain size in TiO2 film. The optical parameters of ALD TiO2 films showed very dependent of the change of crystal phase and roughness, allowing to obtain films with distinct properties for dye-sensitized and perovskite-based solar cells.